Experimental and theoretical approaches for determining the K-shell fluorescence yield of carbon. (January 2023) - Hönicke, Philipp; Unterumsberger, Rainer; Wauschkuhn, Nils; Krämer, Markus; Beckhoff, Burkhard; Indelicato, Paul; Sampaio, Jorge; Marques, José Pires; Guerra, Mauro; Parente, Fernando; Santos, José Paulo
Abstract: The knowledge of atomic fundamental parameters, such as the fluorescence yields with low uncertainties, is of decisive importance in elemental quantification involving X-ray fluorescence analysis techniques. However, especially for the low-Z elements, the available data in the literature is either of poor quality, of unknown or very large uncertainty, or both. For this reason, the K-shell fluorescence yield of carbon was determined in the PTB laboratory at the synchrotron radiation facility BESSY II. In addition, theoretical calculations of the same parameter were performed using the multiconfiguration Dirac–Fock method, including relativistic and quantum electrodynamics (QED) corrections. Both values obtained in this work are compared to the corresponding available published data. Highlights: Determination of carbon K-shell fluorescence yield employing multiple materials. Theoretical calculation of carbon K-shell fluorescence yield. Very good agreement between different results. Significant reduction of its uncertainty as compared to existing data.